If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-15b+1=-13-15b+15
We move all terms to the left:
-15b+1-(-13-15b+15)=0
We add all the numbers together, and all the variables
-15b-(-15b+2)+1=0
We get rid of parentheses
-15b+15b-2+1=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation
| 9x-4-3x-6=5 | | 2(2b+7)=-12+6b | | 4(2x+3)=7x-3x+5 | | M=54m-5 | | -320=x*x=4 | | -25y=-350 | | 15-4w-10=5-4w | | 2x-7+3x-9=14 | | x^2-3x-12+2=0 | | 2t+16=3t-15 | | 5(3x-2)=5x-8 | | 15=9x+42 | | 17r-15=-15+2r+15r | | x+(x*0.04)=50 | | -g=6 | | m-457=327 | | 6n^2-47n-8=0 | | 0=(5b-3)(b+3) | | x^2-3x-12-(-2)=0 | | c-34=3 | | 8^x=2097152 | | 1/5x-4=-6 | | 15t+7=19t-9 | | x^2-3x-12=-2 | | 7-j=-j-4 | | 2014=m*53 | | 2x+4*1/5=9 | | 9x-3=11x-13 | | 12c-16=8c+8 | | -3v/4=6 | | z+20=88 | | 4w-11=3w+10 |